Achilles tendinopathy and plantar fasciopathy: Are we ignoring calcaneal bone morphology? – A radiological assessment of calcaneal parameters. (December 2022) - Devalia, Kailash; Ramaskandhan, Jayasree; Rajeev, Aysha
Abstract: Background: A radiological study was conducted to determine whether calcaneal morphological differences contribute to the pathophysiology of Achilles tendinopathy and plantar fasciopathy. This study is aimed to support our new hypothesis to explain the pathophysiology leading to recalcitrant disease and also to identify the role of calcaneal osteotomy for treating these conditions. Materials and methods: Calcaneal width and height distance deviation from centre of ankle joint rotation was measured on standardised lateral weight bearing Ankle radiographs. A comparison was made between control group and study group to identify the differences in measured parameters. Results: Significant difference (P = 0.05) was observed in calcaneal width distance in study group with Achilles tendinopathy. In Plantar fasciopathy the vertical distance was reduced suggesting flattening of arch in study group. However, the difference was not statistically significant. Conclusion: The study identifies the importance of evaluating calcaneal morphology for patients with recalcitrant Achilles tendinopathy and plantar fasciopathy. A new hypothesis is proposed to explain the high stresses produced in entire Achilles –calcaneus –plantar fascia unit which leads to chronic inflammatory response and intra substance degeneration. Graphical Abstract: ga1 Highlights: Achilles tendinopathy (AT) and Plantar Fasciopathy (PF) are difficult conditions to treat. Conservative and operative treatment gives varying results. Our study is aimed at investigating the role of altered calcaneal morphology and its effect on development of AT & PF. The increased distance of Achilles tendon and plantar fascia attachments produces high tensile stresses and predisposes to degenerations. We suggest the future role of modified block resection calcaneal osteotomy for recalcitrant disease.